Ethnobotany of The Medicinal Plants Used by Panton Luas Community, Samadua Subdistrict, Aceh Selatan - Riza Ulhaq; Nir Fathiya (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Panton Luas community in Aceh Selatan Regency maintains local wisdom on the traditional use of medicinal plants. The study aimed to obtain information about the types of medicinal plants and to know how the plants processed by the Panton Luas community are. The method used Participatory Rural Appraisal (PRA). The results showed that the plants used as medicine consisted of 41 plant species under 32 families. The parts of the plant used consisted of leaves (65%), fruit (18%), stems (5%), flowers (5%), seeds (5%), sap (2%), and rhizomes (2%). Habitus used by local people was trees (34%), herbs (29%), shrubs (29%), and bushes (8%). Medicinal plants used by local people consisted of cultivated plants (73%) and wild plants (27%). The processing was done by grinding (39%), boiling (22%), squeezing (17%), eating directly (12%), dripping (5%), rubbing (3%), and chewing (2%). The use of traditional medicinal plants by the Panton Luas people was to treat various diseases. The ethnobotanical study in the Panton Luas community was the first step to documenting the traditional knowledge of the village community regarding medicinal plants so that it would be transferred to the next generation.